1990
DOI: 10.1161/01.str.21.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow, glucose utilization, and electrocorticograms following common carotid artery occlusion in gerbils.

Abstract: We designed this study to elucidate the relations between cerebral function and glucose metabolism during the eariy stage of ischemia. We induced focal cerebral ischemia in 28 gerbils by occluding the common carotid artery. We recorded electrocorticograms in 34 gerbils by positioning bipolar electrodes between the anterior and middle cerebral arteries. We related the electrocorticograms to local cerebral glucose utilization measured with [ 14 C]2-deoxyglucose in half the gerbils. A characteristic pattern (a zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Consequently, it seems to be possible to properly evaluate the results herein even with the CMRglc values calculated without correction for the altered lumped constant. In particular, the elevated CMRglc observed in this study is obviously true, because such alterations of lumped constants result in the underestimation of CMRglc (Tanaka et al, 1985;Hasegawa et al, 1990;Back et al, 1995).…”
Section: Cbf and Cmrglc In A Primate Stroke Model 207mentioning
confidence: 69%
See 2 more Smart Citations
“…Consequently, it seems to be possible to properly evaluate the results herein even with the CMRglc values calculated without correction for the altered lumped constant. In particular, the elevated CMRglc observed in this study is obviously true, because such alterations of lumped constants result in the underestimation of CMRglc (Tanaka et al, 1985;Hasegawa et al, 1990;Back et al, 1995).…”
Section: Cbf and Cmrglc In A Primate Stroke Model 207mentioning
confidence: 69%
“…4 and 5, Table 2), which was confined to the ipsilateral cortex and was most prominent at the anterior and posterior parietal cortices. In other studies, an elevated glucose metabolism and an uncoupling of flow and metabolism were observed in the arterial borderzone during several hours of acute ischemia (Ginsberg et al, 1977, Tanaka et al, 1985Hasegawa et al, 1990;Back et al, 1995) and were regarded as factors contributing to infarct development (Tanaka et al, 1985;Back et al, 1995). However, these results were obtained primarily from experiments in rodents and cats.…”
Section: Cbf and Cmrglc In A Primate Stroke Model 207mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is an energy-consuming process (Shinohara et al, 1979;Gjedde et al, 1981). Several experiments document the correlation between SD or SD-like electrophysiological changes and en hancement of the glucose utilization in the periph ery of ischemic lesions (Nedergaard and Astrup, 1986;Hasegawa et al, 1990). Glutamate or agonists of the glutamate receptor elicit SD (Van Harreveld, 1959;Lauritzen et al, 1988), and glutamate recep tor antagonists effectively inhibit SD (Goroleva et al, 1987;Lauritzen and Hansen, 1992;Nellgard and Wielock, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…We have reported recently that a CBF and cerebral metabolic rate of glucose uncoupling was observed in the parietal cortex and several regions surrounding the ischemic core in a primate model of thromboembolic stroke (Kuge et al, 2001). Although the mechanisms underlying the elevated glucose metabolism and the process of uncoupling of flow and metabolism remained to be clarified, anaerobic glycolysis and SD are proposed as factors contributing to elevated glucose metabolism in early phases of ischemia (Ginsberg et al, 1977;Shinohara et al, 1979;Tanaka et al, 1985;Hasegawa et al, 1990;Back et al, 1995;Kuge et al, 2000). The contribution of SD to pathophysiology of ischemic stroke cannot be resolved by the findings obtained from the present study.…”
Section: Fig 2 Characteristics Of Spreading Depression Waves (A)mentioning
confidence: 99%